Pengaruh Kemudahan Penggunaan, Konten, dan Gaya Hidup terhadap Keputusan Pembelian melalui Tiktok Paylater (Survei pada Mahasiswa KIP-K Administrasi Bisnis Universitas Wanita Internasional) - Desti Shalsabila; Umi Narimawati (Sekolah Menengah Kejuruan (SMK) Pustek, 2026)
The rapid development of social commerce has reshaped purchasing behavior among university students, particularly through the integration of digital content and deferred payment services. TikTok PayLater offers transactional convenience but may also encourage impulsive consumption, especially among KIP-K scholarship students who face financial constraints. This study aims to analyze the effects of perceived ease of use, TikTok content, and lifestyle on purchase decisions through TikTok PayLater among Business Administration students at Universitas Wanita Internasional. A quantitative associative approach was employed, with data collected from 83 respondents using an online questionnaire. The data were analyzed using multiple linear regression. The results indicate that perceived ease of use, TikTok content, and lifestyle each have a positive and significant effect on purchase decisions. Simultaneously, these variables explain 59.0% of the variance in purchase decisions, with lifestyle emerging as the most dominant influencing factor. The findings suggest that purchase decisions in social commerce environments are shaped not only by technological convenience but also by content exposure and users’ lifestyle characteristics. This study contributes to the understanding of digital consumer behavior and highlights the importance of responsible PayLater usage among university students.